Improving Vocabulary and Reading Comprehension Achievements of Eight Grade of MTS N Baturaja Through Repeated Reading Strategy - Agustiani, Merie (Lentera: Jurnal Ilmiah Kependidikan, 2016)
Having word knowledge is important in reading comprehension to help students understand English text. Repeated Reading (RR) strategy is believed that it can enrich studentsâ vocabulary and reading comprehension achievement. This study aimed at investigating the effects of RR strategy on vocabulary and reading comprehension achievement. Forty eight of eighth graders of MTs Negeri baturaja were chosen as the sample. Each group consists of twenty four students. Vocabulary and reading comprehension tests were administered to the students before and after the interventions. The results showed that there was significant difference in vocabulary and reading comprehension achievements (Ï<0.000) after the interventions.